2019
DOI: 10.1038/s41467-019-10221-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of the circular chromosome in a live bacterium

Abstract: Although the physical properties of chromosomes, including their morphology, mechanics, and dynamics are crucial for their biological function, many basic questions remain unresolved. Here we directly image the circular chromosome in live E. coli with a broadened cell shape. We find that it exhibits a torus topology with, on average, a lower-density origin of replication and an ultrathin flexible string of DNA at the terminus of replication. At the single-cell level, the torus is strikin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 48 publications
5
71
0
Order By: Relevance
“…4b-d). We found that the Left-Ori-Right orientation of chromosomes that was reported earlier in rod-shaped E.coli cells 21,22,23 was preserved in these widened cell too. We observed the origin of replication of single nucleoids to duplicate near the midcell location ( Fig.…”
Section: Chromosome Segregation Depends On the Lateral Confinement Bysupporting
confidence: 81%
See 2 more Smart Citations
“…4b-d). We found that the Left-Ori-Right orientation of chromosomes that was reported earlier in rod-shaped E.coli cells 21,22,23 was preserved in these widened cell too. We observed the origin of replication of single nucleoids to duplicate near the midcell location ( Fig.…”
Section: Chromosome Segregation Depends On the Lateral Confinement Bysupporting
confidence: 81%
“…Since MreB is essential for maintaining the rod shape of E.coli cells 19 , the addition of A22 (which inhibits the MreB polymerisation) results in cells that are significantly wider than normal rod-shaped cells 10,2021 . Our earlier work showed that cells treated with A22 stay physiologically healthy and active, while the single nucleoid adopts a toroidal configuration within the larger available cell volume 21 . Importantly, these cells allow to follow the dynamics of the replisomes and the nucleoid upon re-initiating replication.…”
Section: Independently Moving Replisomes Form a Replication Bubblementioning
confidence: 96%
See 1 more Smart Citation
“…S7). This is consistent with the observation that different genetic markers in ter can localize to distant regions of the same cell (17), with Hi-C data (18), and with analysis of cells with increased volume (16). We summarize the dimensions of MukBEF axial filaments in Fig.…”
supporting
confidence: 88%
“…MukBEF axial cores were also observed in rifampicin-treated cells (reduced molecular crowding) and in cells of increased volume after treatment with A22 ( Fig. S4) (16).…”
mentioning
confidence: 79%